Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question looks so simple, yet it confused me.

If $f(x) = e^{\ln(1/x)}$, then $f'(x) =$ ?

I got $e^{\ln(1/x)} \cdot \ln(1/x) \cdot (-1/x^2)$.

And the correct answer is just the plain $-1/x^2$. But I don't know how I can cancel out the other two function.

share|cite|improve this question
but how do I cancel out the original e and ln ? edit: nvm – user64698 Mar 2 '13 at 20:45
They way you did, use chain rule, $\displaystyle \frac{d}{dx} \left( \log \left( \frac 1 x \right)\right) = ??$ – Santosh Linkha Mar 2 '13 at 20:49
The answers below are the way to go. As to your solution, your second term of $\ln(\frac1x)$ is incorrect. – Mike Mar 2 '13 at 20:52
Yes. I see the solution now. I just can't select my best answer yet in 2 minutes. Thank to all who helped me. – user64698 Mar 2 '13 at 20:53
up vote 6 down vote accepted

Hint: $$\quad e^{\ln(a)}=a\quad $$ Solving the more complicated way also gives the right answer: $$\frac{d}{dx}(e^{\ln(1/x)})=e^{\ln(1/x)}\cdot\frac{d}{dx}(\ln(1/x))=e^{\ln(1/x)}\cdot \left[\frac{1}{1/x}\cdot \frac{d}{dx}(1/x)\right]=\frac{1}{x}\cdot \left[x\cdot \left(-\frac{1}{x^2}\right)\right]$$ where we have used that $$\frac{d}{dt}(e^{f(t)})=e^{f(t)}\left(\frac{d}{dt} f(t)\right)$$ and that $$\frac{d}{dt}(\ln(g(t)))=\frac{1}{g(t)}\left(\frac{d}{dt} g(t)\right)$$

share|cite|improve this answer

Hint: the exponential and logarithm are inverse functions: $$e^{\ln u}=u$$ for any $u>0$.

share|cite|improve this answer

For $a>0$, $e^{\ln(a)} = a.\;\;$ Similarly, $\;\;\ln(e^a) = a\ln(e) = a\;\;$ because for $$\;f(x) = e^x,\;\;f^{-1}(x) = \ln(x)\quad\text{and}\quad g(x) = \ln x,\;\;g^{-1}(x) = e^x$$

That is, $\ln(x)$ and $e^x$ are each others' inverse function on the set of positive real numbers.

share|cite|improve this answer

The other hints provided will help you find the correct solution the easy way.

However, I'd like to point out that your approach has a flaw: $$\frac{d}{dx}\left(e^{f(x)}\right)\ne e^{f(x)}\cdot f(x)$$

Rather, it is: $$\frac{d}{dx}\left(e^{f(x)}\right)= e^{f(x)}\cdot f'(x)$$

Thus, we'd have (this is the hard way, applying the line of thought you tried to use):

$$\begin{align} \frac{d}{dx}\left(e^{\ln 1/x}\right) & = e^{\ln 1/x}\cdot\left(\frac{d}{dx}\left(\ln 1/x\right)\right)\\ & = e^{\ln 1/x}\cdot\left(\frac{1}{1/x}\cdot\frac{d}{dx}\left(1/x\right)\right)\\ & = e^{\ln 1/x}\cdot\left(\frac{1}{1/x}\cdot\left(\frac{-1}{x^2}\right)\right)\\ & = e^{\ln 1/x}\cdot\left(\frac{1}{1/x}\cdot\left(\frac{-1}{x^2}\right)\right)\\ \end{align}$$ This is the correct answer, we don't simplify anything. Simplifying (using the same property as other have hinted that you should use:

$$\begin{align} e^{\ln 1/x}\cdot\left(\frac{1}{1/x}\cdot\left(\frac{-1}{x^2}\right)\right) & = \frac{1}{x}\cdot\left(\frac{1}{1/x}\cdot\left(\frac{-1}{x^2}\right)\right)\\ & = \frac{1}{x}\cdot\left(x\cdot\left(\frac{-1}{x^2}\right)\right)\\ & = \frac{-1}{x^2} \end{align}$$

share|cite|improve this answer

$f(x) = e^{\ln(1/x)}=1/x$, then $f'(x) =(1/x)'=\frac{1'\cdot x-x'\cdot 1}{x^2}=\frac{- 1}{x^2}$

share|cite|improve this answer
Nice my friend. +1 – Babak S. Mar 6 '13 at 11:44

As mentioned by others you use that $$ e^{\ln(x)} = x $$ so that $$ f(x) = \frac{1}{x}. $$ Note here though that the domain of $f$ is all positive numbers. The original expression for $f$ is not defined for negative $f$. So also the domain for the derivative will (only) be all positive numbers.

share|cite|improve this answer
oh well.. Yup, it's that simple, but I don't see it T_T. Thanks all – user64698 Mar 2 '13 at 20:46

Applying the chain rule, one gets $$ \frac{d}{dx} e^{\ln(1/x)} = e^{\ln(1/x)}\cdot \ln'(1/x)\cdot \frac{d}{dx} \frac1x =\cdots\cdots $$ So: $$ \frac{d}{dx} e^{\ln(1/x)} = e^{\ln(1/x)}\cdot \frac{1}{1/x}\cdot \frac{d}{dx} \frac1x =\cdots\cdots $$

You were simply failing to apply the chain rule correctly.

All of the above is of course the hard way. Here's the easy way: $$ \frac{d}{dx} e^{\ln(\text{whatever})} = \frac{d}{dx}(\text{whatever}) = \cdots\cdots $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.